Achieving and maintaining inventory accuracy in a South African Mrp-ii environment - De Freitas, Paulo Jose Felix (My University, 2015)
Achieving and Maintaining Inventory Accuracy in a South African MRP-II Environment, can he realised through the use of Cycle Counting techniques coupled with sophisticated Inventory Management computer systems. These techniques and facilities enable businesses to obtain the 98\ inventory accuracy level, as demanded by the MRP-II strategy. The most common causes of errors in inventory records are identified and recommendations are given on how to locate and eliminate them. Attention is also given to aspects crucial to the success of any corporate goal, like a high inventory accuracy. These aspects include the training of manpower and the educational levels in South Africa, o r those people responsible for the achievement of such goals.